Penanaman Nilai-Nilai Religius dalam Rutinan Hadroh Mashoka (Majelis Sholawat) Putri kecamatan Kuwarasan - Fibriyan Irodati; Khaerum Alfi (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2023)
Religious value is the highest and absolute value, this value is sourced from human beliefs and beliefs. Religious values ​​reflect faith in God Almighty which is manifested in the behavior of carrying out religious teachings and beliefs that they adhere to. Religious values ​​are values ​​regarding the concept of religious or religious life in the form of bonds or relationships that govern humans and their God, while the inculcation of religious values ​​can be through example, namely by following the stories of the Prophet, the birth of the Prophet and the Prophet's Family. Sholawat is a poem of praise and praise for the Prophet Muhammad SAW. The importance of Hadroh Mashoka Putri's routine activities in the Kuwarasan sub-district is as a means of learning to develop religious values ​​as well as to preserve religious culture. This research is a field research, with qualitative research methods. This research was conducted at the Gandusari prayer room, Kuwarasan, Kebumen district. Data collection techniques in this study used interview, observation, and documentation techniques. The interview was conducted by a member of the NU Muslimat in Kuwarasan. The stages of data analysis techniques are data reduction, data analysis, and conclusions. The results showed that the inculcation of religious values ​​through the hadroh Mashoka Putri activities consisted of three stages, namely by conveying or imparting knowledge which was then received, digested and understood by the participants so that it was carried out and carried out in their daily lives. After being applied in daily life, what they know they practice is in accordance with what is their example and what they learn from their role models. Keywords: Religious Values, Sholawat